E-cigarette use-associated lung injury (EVALI) - Tituana, Nathaly Yessenia; Clavijo, Claudia Gabriela; Espinoza, Evelyn Fernanda; Tituana, Viviana Alexandra (Pneumologie, 2023)
The prevalence of vaping has overtaken conventional cigarettes as the most frequent form of nicotine consumption among 15–24-year olds. There are currently a large number of both legitimate and illegitimate products and suppliers offering more than 8000 different flavors of vape on the market, whose additives are not tested, studied or regulated and whose safety and toxicity profile remains unknown. In vitro studies have demonstrated a dose-dependent decrease in the viability of normal human bronchial epithelial cells after exposure to vapor from electronic vape devices.Short- and medium-term studies to date indicate that vapor-induced pulmonary lesions are the most serious and commonly reported side effect; such lesions include bilateral ground glass opacities in lung bases with subpleural preservation, bilateral infiltrates, pleural effusion, pneumomediastinum and nodular opacities. Cases of EVALI have been described in patients with daily exposure, as well as in users who reported having been exposed to these substances at least once a month. The most frequently inhaled substances are THC, flavored liquids of unknown content, and nicotine.The clinical manifestations of dyspnea and cough are the most frequent respiratory symptomatology, in addition to constitutional manifestations such as fever and chills, and gastrointestinal manifestations such as vomiting, nausea, abdominal pain and diarrhea. To these can be added the presence of tachypnea, tachycardia, elevated blood pressure, hypoxia, leukocytosis with neutrophilia and elevated ESR.
Keywords: Electronic Nicotine Delivery Systems; Lung injury; Vaping